Nurse’s work engagement: Does job feedback matters? - Othman, Noraini; Ghazali, Zahiruddin; Ahmad, Sa'ari (2013)
Nurses play an important role in delivering quality healthcare services to the patients. They form the main and biggest group of healthcare professionals. This study examined the relationship between job feedback and work engagement using a sample of 290 staff nurses working in two public hospitals in Peninsular Malaysia. Statistical results using regression analysis indicated that job feedback was positively related to work engagement. Implications of the results are discussed, together with the limitations and suggestions for future research.